Preparation, antioxidant potential and angiotensin converting enzyme (ACE) inhibitory activity of gum arabic-stabilized magnesium orotate nanoparticles - Abdelkader, Hassani; Hussain, Siti Aslina; Abdullah, Norhafizah; Kamarudin, Suryani; Rosli, Rozita (Faculty of Food Science & Technology, UPM, 2020)
The present work investigated the antioxidant properties and antihypertensive activity of magnesium orotate (MgOr) using various established in vitro assays, such as β-carotene bleaching activity, 1,1-diphenyl-2-picrylhydrazyl (DPPH), and nitric oxide scavenging activity as well as angiotensin converting enzyme (ACE) inhibitory activity. Magnesium orotate nanoparticles (MgOrGANPs) were prepared using the gum arabic (GA) as stabiliser coatings for nanoparticles through freeze-drying method. The in vitro cytoxicity of MgOrGANPs against human breast cancer MCF7, liver cancer HepG2, and colon cancer HT29 was investigated. The nitric oxide (NO) and DPPH scavenging assays of MgOrGANPs showed a dose-dependent trend, while 500 and 200 µL/mL were significantly more effective than the other concentrations with an IC50 of 89.56 µg/mL and 63.22% DPPH scavenging capacity respectively. The exposure of human cancer cells to MgOrGANPs at 1.56 – 1,000 µg/mL using 3-)4,5-dimethylthiazol-2-yl(2,5-diphenyl tetrazolium bromide (MTT) inhibited the growth of cell lines examined in a dose-dependent manner. Hence, MgOrGANPs may have great potential to be applied for cancer treatments.